Pendampingan Diversifikasi Olahan Ikan Beong (Hemibagrus nemurus) Kaleng Kuliner Khas Borobudur dengan Metode Pasteurisasi pada UMKM sebagai Upaya Peningkatan Ekonomi Berbasis Gastronomy Tourism - Azis Ikhsanudin; Lolita Lolita; Putri Rachma Novitasari (Universitas Muhammadiyah Semarang, 2024)
Magelang Regency, a cultural and heritage-based tourist destination, holds significant potential for developing Gastronomy Tourism. One notable product is beong fish, internationally refered as asian redtail fish. Beong fish (Hemibagrus nemurus), a culinary specialty of the Progo River. However, several challenges hinder its development, including unmet tourist demand for beong fish as a Borobudur souvenir due to short shelf life, lack of partner skills in diversifying products into canned beong fish, and reliance on traditional marketing systems. The mentoring program aims to address these issues through training in pasteurization and halal certification. Results from pre and post-tests indicate an increase in partners' knowledge. The average pre-test score for pasteurization training was 5.8 ± 3.966, rising to 10.1 ± 3.107 in the post-test. Similarly, for halal certification, the pre-test average was 8 ± 4.546, improving to 11.6 ± 2.757 post-test. Statistical analysis revealed significant differences (P<0.05), with a value of 0.002, in partners' knowledge before and after training. In conclusion, the training and mentoring program successfully enhanced partners' knowledge of the pasteurization process and halal certification, supporting the diversification and development of canned Mangut Beong as a potential Borobudur souvenir.